Síndrome de Garcin relacionada a linfoma não-Hodgkin - Resende, Lucilene Silva Ruiz e [UNESP]; Gepp, R. A. [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Rocha, Fernando Coronetti Gomes da [UNESP]; Bacchi, M. M. [UNESP]; Niéro-Melo, L. [UNESP] (My University, 1998)
The complete unilateral cranial nerve paralysis syndrome, or Garcin 's Syndrome, is a rare clinical condition. The purpose of this paper is to describe a case associated with non-Hodgkin s lymphoma. A 41-year-old male patient developed a progressive cranial nerve disorder. On the right hand side, there was impairment of all cranial nerves. We report the clinical and laboratorial findings. Lymph node exeresis revealed a Diffuse Non-Hodgkin s Lymphoma, with diffuse hone marrow infiltration. Cerebrospinal fluid showed pleocytosis, with 100% of immunoblasts. The CT scan showed no tumoral masses on the brain stem. This is the first clinical description of a complete Garcin 's Syndrome caused by diffuse lymphomatous infiltration of the cranial nerves.
Garcin's syndrome related to non-Hodgkin 's lymphoma
Keywords: Garcin's syndrome; Non-Hodgkin's lymphoma